Efficient Flow Synthesis of Glycidyl Ether Using BuSnCl3 as a Mild Lewis Acid - Kasakado, Takayoshi; Nakamura, Masahito; Nishizawa, Akihiro; Hosomi, Tetsuya; Ryu, Ilhyong; Fukuyama, Takahide (Synthesis, 2024)
A ring-opening protocol of epichlorohydrin with 2-ethylhexanol was investigated for the synthesis of the corresponding chlorohydrin ether. BuSnCl3 proved to be an efficient mild Lewis acid catalyst, yielding the product with high selectivity. A scalable flow synthesis was achieved by modifying the flow setup. The flow synthesis of the corresponding glycidyl ether from the chlorohydrin ether was also carried out in an efficient manner by using the basic treatment.
Keywords: flow synthesis; glycidyl ethers; epichlorohydrin; BuSnCl3; Lewis acids; chlorohydrin